Kegiatan Bimbingan Belajar dalam Meningkatkan Minat Belajar Siswa di SMP Iceya Ndaha - Napfiah, Siti; Kalli, Yohanes Ndara; Sulistyorini, Yunis; Kartika, Era Dewi; Surahman, Harry (Universitas Muhammadiyah Tangerang, 2025)
Tutoring plays an important role in the development of children's learning, because not only what is obtained at school, learning outside of school has a considerable impact and influences student learning motivation. Non-formal education is expected to increase students' interest or interest in learning. In non-formal education students are invited to study with methods that are different from formal education in general, non-formal education is more relaxed and attractive by introducing something new or what they don't understand with interesting things, in contrast to formal education, learning is more fun by playing games as a distraction and also as an insert in learning. Students are not only required to be able to memorize but also must understand and be interested because by being interested students themselves find out what they don't know. For this reason, the application of learning using the learning and playing method can motivate students in learning to become individuals who are more creative and active in thinking and also solving problems.